Air Pollution Airshed Map of the Chaurjahari Model City, Rukum West, Karnali, Nepal (Journal of Nepal Physical Society, 2023)
Chaurjahari area of the Rukum West District of the Karnali Province is one of the proposed model cities of the Government of Nepal, being developed to manage the unbalanced, rapid, haphazard, and uncontrolled urbanization in Nepal. While the model city plans to integrate physical, social, economic, and other anticipated urban facilities, no necessary thoughts on the protection of air quality seem to be given. The present study has been conceived to understand the meteorological implications of air pollution transport and the formation of pollutant fields over Chaurjahari City using weather and chemical transport modeling. The meteorological fields and pollution transport were simulated with the Advanced Weather Research and Forecasting (WRF-ARW) modeling system and an Eulerian Chemical Transport Model (CTM), respectively. The WRF simulated fields displayed a strong diurnal pattern with windless conditions throughout the early morning to late morning hours, whereas, strong winds accompanied the significant up and downndrafts in the afternoon. Similarly, the pollution dispersion simulation revealed that the city area remains stagnated blanketing the city area from early morning to noontime deteriorating air quality. However, in the afternoon time, local meteorological flows over the area generally organize pollutants transport towards the northern and northeastern high mountainous region reducing air pollution but risking deposition of pollutants in the mountain glaciers. Such deposition of pollutants over the mountains may accelerate the melting of glaciers and snow enhancing the effects of climate change.